Microstructural Evolution of Aluminum-A356 Alloy with and Without Sic Reinforcement Submitted to Mechanical Milling [Evolución Microestructural de Una Aleación de Aluminio a356 Con y Sin Reforzamiento de Sic Sometida a Molienda Mecánica] - Palominos-Belmar, P; Bustos-Castillo, O; Ordonez, S; Martinez-Catalan, F; Fernandez-Echevarria, H (Universidade Federal do Rio de Janeiro, 2018)
The effect of milling time on the crystallite size, microstrain and Vickers microhardness, of an aluminum alloy A356 (Al-7wt % Si) with and without SiC reinforcement (15 wt%) was studied. The metal alloy powders were obtained by the rotating electrode process (REP) from cylinders of the alloy, the obtained powders present spherical morphology with an average size of 150 μm and an average microhardness of 94 HV0,1. The alloy with and without reinforcement was subjected to mechanical milling in a high energy mill SPEX 8000D with effective milling times of 3, 6, 9 and 12 hours. The microstructural evolution of the obtained samples was evaluated by X-ray diffraction, Vickers microhardness and optical microscopy. It is noted that the values of microhardness of the alloy with and without reinforcement milling for 3 hours are very similar; for higher milling times, samples reinforced with SiC reach higher values than the samples without reinforcement. This increase in the microhardness is achieved thanks to the uniform distribution of reinforcement particles, the strain hardening of the metal matrix and microstructural refinement produced by mechanical milling. It is appreciated that the composite reaches a crystallite size somewhat smaller than the alloy, although both show similar behavior. The crystallite size presents a rapid decrease in the early hours of milling and then remains almost constant. © 2018, Universidade Federal do Rio de Janeiro. All rights reserved.